2000
DOI: 10.1001/archinte.160.16.2471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical Parameters to Predict Mycobacterium tuberculosis in Inpatients

Abstract: Among inpatients with suspected active pulmonary TB, a prediction rule based on clinical and chest radiographic findings accurately identified patients requiring respiratory isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 26 publications
2
66
1
2
Order By: Relevance
“…After full-text review, 174 articles were excluded for various reasons and 13 articles (all observational studies) were included in the systematic review ( fig. 1) [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After full-text review, 174 articles were excluded for various reasons and 13 articles (all observational studies) were included in the systematic review ( fig. 1) [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 included studies, 12 studies involved scoring systems that combined clinical and radiographic features [20][21][22][23][24][25][26][27][28][29][30][31] and one study involved validation of 13 clinical prediction rules for inpatient respiratory isolation [32]. This study was included as it retrospectively applied prediction rules from six studies identified by our systematic review to a group of eligible participants with symptoms suggestive of PTB.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore used the more stringent definition that a strong TST response with an induration in the TST of ⩾14 mm equated to LTBI [27]. Using this definition, it was also found that a strong TST response (⩾14 mm) was associated with a significantly elevated risk for subsequent progress to TB among contacts, as described previously [28].…”
Section: Discussionmentioning
confidence: 99%
“…For patients whose samples were Xpert-positive and culture-negative, medical records were examined for clinical diagnosis of TB [8,9]. Patients with radiological and/or histological signs suggesting TB were considered TB cases only if a clinical improvement after anti-TB treatment was recorded.…”
Section: Methodsmentioning
confidence: 99%